Copyright law issues in the context of video game Let's Plays and livestreams. (December 2020) - Tie, Anna-Lisa
Abstract : Video game content has grown increasingly popular on internet service providers such as YouTube and Twitch. This genre of uploaded material includes the gameplay of internet users, in the form of pre-recorded 'Let's Play' videos, as well as livestreamed playthroughs. However, the application of current copyright law principles to these kinds of content is still a grey area. This legal uncertainty can be attributed to the absence of binding judicial precedent on whether video game Let's Plays and livestreams constitute copyright infringement or fair use. More recent legislative provisions intended to update copyright law for current digital technology provide little assistance, as their implementation by internet platforms has perpetuated a practice of favouring the interests of game developers over users who produce Let's Plays and livestreams. This article discusses the problems of applying existing copyright law to video game playthroughs uploaded online, as well as the drawbacks of the automated tools YouTube and Twitch have developed to manage these types of content in their systems. In order to address these issues, suggestions for copyright law reform will be explored. However, in the absence of imminent legislative amendments, I conclude that compulsory licensing arrangements, and making modifications to YouTube's and Twitch's content scanning tools are the most viable means of achieving a better balance between the interests of game developers, the internet platforms, and Let's Play creators and game streamers.